Analysis of the World Experience of Digital Transformation of Industry: Institutional Model - I. A. Zubritskaya (Цифровая трансформация, 2019)
The article describes the world experience of implementation technical and technological means of the fourth industrial revolution in industry. The main practical approaches to the digital transformation of industry are systematized, the key trends of the existing mechanisms digital transformation of industrial production are highlighted. Based on the results of the analysis, an institutional model of the organizational and economic mechanism digital transformation of the manufacturing industryRepublicof Belarusis proposed.